2018
DOI: 10.1007/s00265-018-2457-y
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of food abundance and weather on the growth of a sub-arctic shorebird chick

Abstract: The relative importance of food abundance and weather on the growth of a sub-arctic shorebird chick Machin, Paula; Fernandez-Elipe, Juan; Klaassen, Raymond H. G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(62 reference statements)
0
11
3
Order By: Relevance
“…As a result, warmer temperatures can result in faster growth rates of shorebird chicks Pearce-Higgins & Yalden, 2002Schekkerman et al, 1998Schekkerman et al, , 2003Senner et al, 2017). However, our results and others (Machín, Fernández-Elipe, & Klaassen, 2018) Additionally, we do not know how food availability relates to growth and survival of older chicks (i.e., >10 days old). Indeed, greater food requirements of older, larger chicks may make them even more vulnerable to food shortages.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…As a result, warmer temperatures can result in faster growth rates of shorebird chicks Pearce-Higgins & Yalden, 2002Schekkerman et al, 1998Schekkerman et al, , 2003Senner et al, 2017). However, our results and others (Machín, Fernández-Elipe, & Klaassen, 2018) Additionally, we do not know how food availability relates to growth and survival of older chicks (i.e., >10 days old). Indeed, greater food requirements of older, larger chicks may make them even more vulnerable to food shortages.…”
Section: Discussioncontrasting
confidence: 62%
“…As a result, warmer temperatures can result in faster growth rates of shorebird chicksPearce-Higgins & Yalden, 2002Schekkerman et al, 1998Schekkerman et al, , 2003Senner et al, 2017). However, our results and others(Machín, Fernández-Elipe, & Klaassen, 2018) suggest that daily weather is less important to shorebird chick growth than is invertebrate availability. Any positive effects warmer temperatures may provide could be negated by increased phenological mismatch between timing of shorebird hatch and invertebrate availability.Additional studies are needed to better understand how chick survival rates relate to food availability and seasonal weather patterns.…”
contrasting
confidence: 48%
“…A phenological mismatch between the timing of reproduction and the period during which these arthropods are abundant is one of the key hypothesised effects of climate change on Arctic insectivores (Tulp and Schekkerman 2008;Saalfeld and Lanctot 2017), with some evidence of reduced growth rates of chicks due to mismatch (McKinnon et al 2012), and reduced body size of juvenile red knots during years of early snowmelt in high Arctic Siberia (van Gils et al 2016). However, there is considerable disagreement among studies; Hudsonian godwits (Limosa haemastica) in Alaska remain appropriately timed with respect to arthropods (Senner et al 2017), sanderling (Calidris alba) chicks in Greenland have not been affected by the apparent mismatch documented there (Reneerkens et al 2016), and there is evidence that temperature increases can alleviate some of the negative effects of phenological mismatch for waders via reduced thermoregulation costs (McKinnon et al 2013), although such thermoregulatory benefits might be minor (Machín et al 2018). Overall, despite the hypothesised importance of mismatch, there is considerable variation both in the extent of mismatch across species, and in the strength of evidence for its effects, perhaps due to variable influence of local environmental drivers across study sites, or life-history traits across species.…”
Section: Climate-related Mismatch As a Stressormentioning
confidence: 99%
“…But evidence linking warm springs with increased nesting success is equivocal; Weiser et al (2018a) found limited evidence for such a relationship, with only two of 14 species investigated across a broad geographic region of the Arctic having higher nest survival in warm springs. The availability of invertebrates also directly affects the ability of young to forage and survive, with mismatches between invertebrate availability and chick hatching predicted to be especially decoupled in early springs when shorebirds do not arrive early enough to time their breeding efforts with invertebrate availability (McKinnon et al, 2012;Machín et al, 2018;Kwon et al, 2019;Saalfeld et al, 2019).…”
Section: Introductionmentioning
confidence: 99%